Arrangements for adult service users who are homeless in English mental health trusts. Issue 1 (12th March 2018) - Lucas, Steven; Archard, Philip John; Tangen, James; Murphy, David
Abstract : Purpose: The purpose of this paper is to report an analysis of arrangements in English mental health trusts to meet the needs of adult service users who are homeless. Homelessness is associated with various forms of mental ill-health, yet homeless people are not always well-served by statutory mental health services. In recent years, practice guidance seeking to improve health outcomes for the homeless has emphasised the need for NHS services to improve care pathways and professional provision for this service user group, in part by collaborating more closely with homelessness organisations. Design/methodology/approach: Responses to freedom of information requests sent to trusts were analysed. The requests asked trusts for information concerning partnerships with external agencies, particular projects/staff, training available to trust professionals, referral pathways, and intervention models/approaches informing work with homeless service users. Findings: In total, 49 trusts provided information that could be used in the analysis. Just under half of these had dedicated arrangements or resources, including outreach teams and clinical staff co-located in accommodation and support services for the homeless. The remaining trusts indicated that they either had some limited specific arrangements, such as links between local agencies working with the homeless and existing services, or no dedicated arrangements in place. Training to improve staff awareness around, and knowledge in, working with homeless service users tended to be minimal if provided at all. Originality/value: This analysis further evidences gaps in the way the needs of the homeless population are addressed by statutory mental health services and adds support to concerns about the homeless having equitable access to care and treatment.